Sensitivity of the Inhomogeneous Magnetization Transfer Imaging Technique to Spinal Cord Damage in Multiple Sclerosis - Rasoanandrianina, H.; Demortière, S.; Trabelsi, A.; Ranjeva, J.P.; Girard, O.; Duhamel, G.; Guye, M.; Pelletier, J.; Audoin, B.; Callot, V. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: The inhomogeneous magnetization transfer technique has demonstrated high specificity for myelin, and has shown sensitivity to multiple sclerosis-related impairment in brain tissue. Our aim was to investigate its sensitivity to spinal cord impairment in MS relative to more established MR imaging techniques (volumetry, magnetization transfer, DTI).MATERIALS AND METHODS: Anatomic images covering the cervical spinal cord from the C1 to C6 levels and DTI, magnetization transfer/inhomogeneous magnetization transfer images at the C2/C5 levels were acquired in 19 patients with MS and 19 paired healthy controls. Anatomic images were segmented in spinal cord GM and WM, both manually and using the AMU40 atlases. MS lesions were manually delineated. MR metrics were analyzed within normal-appearing and lesion regions in anterolateral and posterolateral WM and compared using Wilcoxon rank tests and z scores. Correlations between MR metrics and clinical scores in patients with MS were evaluated using the Spearman rank correlation.RESULTS: AMU40-based C1-to-C6 GM/WM automatic segmentations in patients with MS were evaluated relative to manual delineation. Mean Dice coefficients were 0.75/0.89, respectively. All MR metrics (WM/GM cross-sectional areas, normal-appearing and lesion diffusivities, and magnetization transfer/inhomogeneous magnetization transfer ratios) were observed altered in patients compared with controls (P < .05). Additionally, the absolute inhomogeneous magnetization transfer ratio z scores were significantly higher than those of the other MR metrics (P < .0001), suggesting a higher inhomogeneous magnetization transfer sensitivity toward spinal cord impairment in MS. Significant correlations with the Expanded Disability Status Scale (ρ = –0.73/P = .02, ρ = –0.81/P = .004) and the total Medical Research Council scale (ρ = 0.80/P = .009, ρ = –0.74/P = .02) were observed for inhomogeneous magnetization transfer and magnetization transfer ratio z scores, respectively, in normal-appearing WM regions, while weaker and nonsignificant correlations were obtained for DTI metrics.CONCLUSIONS: With inhomogeneous magnetization transfer being highly sensitive to spinal cord damage in MS compared with conventional magnetization transfer and DTI, it could generate great clinical interest for longitudinal follow-up and potential remyelinating clinical trials. In line with other advanced myelin techniques with which it could be compared, it opens perspectives for multicentric investigations.AMUAix-Marseille UniversityCSAcross-sectional areasEDSSExpanded Disability Status ScaleFAfractional anisotropyHChealthy controlsihMTinhomogeneous magnetization transferihMTRinhomogeneous magnetization transfer ratioλ//axial diffusivityλ⊥radial diffusivityMRCMedical Research CouncilMTmagnetization transferMTRmagnetization transfer ratioNAnormal-appearingSCspinal cordTWTTimed 25-Foot Walk TestSCTSpinal Cord Toolbox